2007
DOI: 10.1136/adc.2006.114207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials: the viewpoint of children

Abstract: The views of 30 children (8-16 years old) attending paediatric medical clinics on paediatric clinical trials were determined by semi-structured interviews. Nineteen children recognised that there were risks involved with taking part in clinical trials. Risks concerned with being paid were recognised by all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Our previous research involved children attending clinics, who were keen to participate in the discussion by consenting for research 4. Our involvement of children in a secondary school suggests they are happy to take part in discussions about health and treatments and that society should try and create more opportunities for young people to be involved in decision-making about issues that affect them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research involved children attending clinics, who were keen to participate in the discussion by consenting for research 4. Our involvement of children in a secondary school suggests they are happy to take part in discussions about health and treatments and that society should try and create more opportunities for young people to be involved in decision-making about issues that affect them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that children are capable of understanding medicine-related topics 2 3. We have previously studied the viewpoint of children attending hospitals as outpatients and found many were able to understand some of the principles that arise in clinical trials 4. We therefore wished to determine whether the viewpoint of children with a chronic illness in relation to clinical trials was different to that of healthy children.…”
mentioning
confidence: 99%
“…In considering the future involvement of patients in clinical trials, it is important that we consider the experiences of families who have recently been involved in optional research studies and investigate the positive and negative experiences of participation. Previous work in this area includes studies assessing the views of parents on consent and participation in therapeutic trials for cancer and other illnesses, but very few studies have been published focusing on the views of both patients and parents of participation in nontherapeutic trials purely in an oncology setting.…”
Section: Introductionmentioning
confidence: 99%
“…Some show that children, when asked, are positive about participation in research that is not directly beneficial to themselves (Wendler, Abdoler, Wiener, & Grady, 2012; Wendler & Jenkins, 2008). Others have examined factors influencing decisions about whether to participate—providing children and adolescents with a number of research scenarios (Cherill et al, 2007; Mukattash, Trew, Hawwa, & McElnay, 2012; Varma, Jenkins, & Wendler, 2008). Others have studied factors related to informed consent and children’s understanding of research information (Bernhardt, Tambor, Fraser, Wissow, & Geller, 2003; Brody, Scherer, AnNett, & Pearson-Bish, 2003; Chappuy, Doz, Blanche, Gentet, & Tréluyer, 2008).…”
mentioning
confidence: 99%